Analysis of the Contribution of LLR Seasoning Business Towards Absorption and Poverty Reduction in the Village Area of Putat, Tanggulangin District, Sidoarjo Regency - Satunggale Kurniawan; Ahmad Zainul Ihsan Arif; Siti Hairunnisyak (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study analyzes the contribution of Seasoning LLR, a local small and medium enterprise (SME), in Putat Village, Tanggulangin District, Sidoarjo Regency, to employment and poverty reduction. Using a mixed-methods approach, quantitative data were obtained from a structured questionnaire distributed to 35 respondents, while qualitative data were collected through in-depth interviews and observations. The study findings indicate that Seasoning LLR plays a significant role in providing employment, particularly for women and individuals with low educational backgrounds. Approximately 46% of respondents work in Seasoning LLR, making it a key driver of local economic activity. This enterprise not only contributes to increased income but also empowers women by integrating them into productive economic activities. However, the study also identified challenges, including limited capital, inadequate marketing strategies, and low human resource capacity. Although employment absorption is evident, its impact on income growth remains relatively small, with only 38% of workers experiencing an increase in income. Therefore, innovation in product development, digital marketing expansion, and skills training are important strategies to increase the contribution of this business. Overall, Seasoning LLR demonstrates potential as a community-based model for sustainable poverty alleviation and rural economic empowerment.